Human factors engineering design demonstrations can enlighten your RCA team. Issue 2 (1st April 2003) - Gosbee, J; Anderson, T
Abstract : A case study is presented, based on the experience of the US Veterans Affairs health system, which shows the benefits of healthcare personnel understanding human factors engineering (HFE) and how it relates to patient safety. After HFE training, personnel are better able to use a systems-oriented approach during adverse event analysis. Without some appreciation of HFE, the focus of adverse event analyses (e.g. root cause analysis (RCA)) is often misguided towards policies or an individual's shortcomings, leading to ineffective solutions. The case study followed the investigation by an RCA team of a retained sponge following cardiac surgery. The team began with a focus on the specific failings of the surgical nurse and outdated policies. HFE design demonstrations were used to redirect the team's focus to more systems-oriented issues, which could be uncovered even when events appeared to be related to policy or training, and to point them towards examining the design of systems that contributed to the event. The team was thus able to identify design flaws and make improvements to the design of the forms and computer systems that were key to preventing such events from recurring.